The Impression of Job Training and Work Motivation Effect at PT. Aksata Satya Pratama Jakarta - Mulyapradana, Aria; JuwitaRamadani Fitria; Mujibul Hakim; S.Thoriqul Huda (Publisher Cv. Inara, 2020)
This research intends to determine the effect of job training and work motivation on performance at PT. Aksata Satya Pratama. To produce quality employees and good performance, companies need to pay attention to increasing knowledge by providing job training. The job training program at PT. Aksata Satya Pratama is still not optimal so that it has an impact on decreased employee performance. Respondents in this research were 40 people and used census techniques. Testing data in this research used validity test, reliability test, classic assumption test (multicollinearity test), multiple linear regression test and hypothesis testing and data analysis in this research using SPSS version 19 program. The results of the research show that job training variables have a negative value (H1 is rejected) and work motivation has a positive value (H2 is accepted). This means that the training variable has no influence on employee performance and work motivation has an influence on employee performance by 67.1%. So, it is stated that job training has no significant effect on employee performance while work motivation has a significant effect on employee performance. In this research, researchers concluded that employee performance will increase supported by employee motivation by factors of work results that are recognized as proven by employees being able to complete various kinds of work.